2012
DOI: 10.1371/journal.pone.0038648
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-31* Is Negatively Associated with Recurrent/Newly Formed Oral Leukoplakia

Abstract: BackgroundOral leukoplakia (OLK) is a potentially malignant disorder of the oral cavity. However, the underlying mechanism of OLK is still unclear. In this study, we explore possible miRNAs involved in OLK.Methodology/Principal FindingsUsing miRNA microarrays, we profiled miRNA expression in OLK and malignantly transformed OLK (mtOLK) tissue samples. The upregulation of miR-31*, miR-142-5p, miR-33a, miR-1259, miR-146b-5p, miR-886-3p, miR-886-5p, miR-519d, and miR-301a along with the downregulation of miR-572, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 49 publications
(65 reference statements)
3
46
0
3
Order By: Relevance
“…The downregulation of miR-623 expression levels in malignantly transformed oral leukoplakia has previously been observed (41). However, in the present study, miR-623 was significantly upregulated in tumor tissues compared with adjacent normal tissue (P<0.01; Fig.…”
Section: A B C Dsupporting
confidence: 54%
“…The downregulation of miR-623 expression levels in malignantly transformed oral leukoplakia has previously been observed (41). However, in the present study, miR-623 was significantly upregulated in tumor tissues compared with adjacent normal tissue (P<0.01; Fig.…”
Section: A B C Dsupporting
confidence: 54%
“…1, b). A decrease of miR-1184 expression is detected in malignant transformation of leukoplakia of the oral cavity [15]. No more data on the relationship between malignant tumors and hsamiR-1184 seems to be available.…”
Section: Resultsmentioning
confidence: 99%
“…This was again a limited study of 12 patients but suggests that miRNAs could be used as a signature to stratify leucoplakia at risk of malignant transformation. Xiao et al found a panel of 72 upregulated and 50 downregulated miRNAs when comparing oral leucoplakia (ranging from non-dysplastic to severely dysplastic) to OSCC [149]. Though these were all significantly differentially expressed, the level of fold-change (e.g.…”
Section: Precancermentioning
confidence: 99%